The complete chloroplast genome sequence of Swertia japonica (Schult.) Makino (Gentianaceae) - Watanabe Yoichi (Mitochondrial DNA. Part B. Resources, 2023)
AbstractSwertia japonica (Schult.) Makino is a traditional medicinal plant in Japan for which the chloroplast genome has not been previously reported. The complete chloroplast genome of S. japonica was determined using a high-throughput sequencing technique. The total length of the S. japonica chloroplast genome was 153,208 bp, and comprised a large single-copy region of 83,319 bp, and a small single-copy region of 18,375 bp, separated by a pair of 25,757 bp inverted repeat regions. A phylogenetic analysis, based on the obtained chloroplast genome, indicated that S. japonica is closely related to S. diluta, S. franchetiana, S. kouitchensis, S. mussotii, and S. punicea. The presented chloroplast genome will be useful for further taxonomic, pharmacological and evolutionary studies of Swertia.